Deuterium retention in re-solidified tungsten and beryllium. (January 2019) - Yu, J.H.; Simmonds, M.J.; Baldwin, M.J.; Doerner, R.P.
Highlights: Deuterium retention in sequentially laser-melted and plasma-exposed tungsten and beryllium is lower in re-solidified material. In tungsten, the deuterium desorption rate from the 1.8 eV trap during controlled thermal desorption is reduced in re-solidified tungsten compared to the reference samples by up to 77%. The reduction is due to annealing of intrinsic defects that grow to larger scale during plasma exposure. In re-solidified beryllium, deuterium retention is reduced by 40% due to a shallower deuterium diffusion depth compared to a reference sample. Abstract: Leading edges of the ITER tungsten (W) divertor are expected to melt due to transient heat loads from edge localized modes (ELMs), and melting of the entire divertor surface will occur during vertical displacement events (VDEs) and disruptions. In addition, understanding tritium retention in plasma facing materials is critical for the successful operation of ITER due to safety reasons. Thus, the question of how melting affects hydrogenic retention is highly relevant for fusion devices. Here we use an Nd:YAG laser to melt tungsten and beryllium in vacuo, and the samples are subsequently exposed to deuterium plasma with sample temperatures ranging from 370 to 750 K. The deuterium content in re-solidified and reference (no laser) samples is measured using thermal desorption spectroscopy and modeled using TMAP-7. In all cases, the re-solidified samples have lower retention compared to the reference samples. For re-solidified tungsten, the most significant effect is in the 1.8 eV trap with peak thermal desorption temperature of ∼750 K, which had a 77% reduction in the peak release rate compared with the reference sample. SEM imaging indicates that laser melting and re-solidification of tungsten anneals intrinsic defects that act as nucleation sites for larger-scale defects that develop during plasma exposure. However, melting does not significantly affect traps with lower de-trapping energies of 1.0 eV and 1.4 eV. In beryllium, melting and cracking results in lower retention compared to the reference sample by 40%, and thermal desorption profiles indicate that the diffusion depth of deuterium into re-solidified beryllium is lower than that of the reference sample.